1996
DOI: 10.1097/00007890-199601150-00018
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic Assessment of Mycophenolic Acid-Induced Immunosuppression by Measurement of Inosine Monophosphate Dehydrogenase Activity in a Canine Model

Abstract: The combination of pharmacokinetic and pharmacodynamic (measurement of the biological effect) monitoring of immunosuppressive drugs provides a method for the optimization of drug dosing. We chose to investigate this using mycophenolic acid (MPA), an immunosuppressive drug that mediates its effect by the inhibition of inosine monophosphate dehydrogenase (IMPDH), a key enzyme in the de novo biosynthesis of purines. Using an assay developed for measurement of IMPDH activity in whole blood, the concentration requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 18 publications
5
68
1
Order By: Relevance
“…21,22 In the present study, only two dogs were analyzed after nonmyeloablative HSCT in this time frame and a secondary maximum could not be observed. In fact, MPA concentrations at 4 h were already in the range of lower limit of detection.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…21,22 In the present study, only two dogs were analyzed after nonmyeloablative HSCT in this time frame and a secondary maximum could not be observed. In fact, MPA concentrations at 4 h were already in the range of lower limit of detection.…”
Section: Discussionmentioning
confidence: 78%
“…Body weight-adjusted apparent oral clearance of MMF following HSCT seems to be comparable between dogs and humans. 16 As in healthy humans a longer median MPA half-life and a considerably higher AUC of 8.1 h and of 62.3 mg/l h were calculated in healthy dogs, 21 respectively, demonstrating the comparability of the canine HSCT model with the clinical situation.…”
Section: Discussionmentioning
confidence: 80%
“…Until recently, little was known about the effects of MPA on IMPDH enzyme activity (21,39,40,41), but an assay method has now been devised which is suitable for the evaluation of the pharmacodynamic effects of MPA (22,27). Previous studies have shown large intraindividual and interindividual differences in IMPDH activity (21,22,27,38,41).…”
Section: Pharmacokinetics/pharmacodynamics Of Ec-mps Versus Mmfmentioning
confidence: 99%
“…However, there is extensive intraindividual and interindividual variation in MMF pharmacokinetics (16)(17)(18)(19). Because IMPDH is inhibited by MPA, pharmacodynamic determination of the extent of inhibition of the enzyme may provide a better indicator of the degree of immunosuppression than measurement of plasma MPA concentrations (19)(20)(21). A specific and reliable nonradioactive method for determination of IMPDH enzyme…”
Section: Introductionmentioning
confidence: 99%
“…This nonradioactive method for specific measurement of IMPDH activity in isolated peripheral mononuclear cells was developed by direct chromatographic determination of produced xanthosine 5'-monophosphate (XMP). In the canine model MPA in therapeutic doses leads to an 50% inhibition of IMPDH-activity (67) . Application of a single dose of 1 g MMF in dialysis patients resulted in a significant inhibition of IMPDH activity in lysed mononuclear cells.…”
Section: Inhibition Of Impdh-activitymentioning
confidence: 99%